PENGARUH PENAMBAHAN EKSTRAK KAYU SECANG (Caesalpinia sappan L.) DAN MINYAK IKAN LEMURU SEBAGAI ADITIF PAKAN TERHADAP PERFORMA TELUR DAN PRODUKTIVITAS PUYUH - Liana Indah Lestari; Agustina Widyasworo; Nita opi ari kustanti (AVES: Jurnal Ilmu Peternakan, 2018)
This research aimed is to determine the effect of Secang extract addition and sardinella fish oil as feed additive on eggs performance and production of quail. The 98 quails and 10 weeks divided into 4 groups with unequal replication using the completely randomized design. The treatment which are P0 (based ration), P1 (based ration + 0,2% secang extract + 4% sardinella fish oil), P2 (based ration + 0,4% secang extract + 4% sardinella fish oil), P3 (based ration + 0,6% secang extract + 4% sardinella fish oil). The parameters observed were length storage time of egg, egg cholesterol rate, feed consumption, egg weight, hen day production, egg mass, feed conversion and mortality. Data were analyzed by ANOVA and Duncan’s analysis. The results showed that Secang extract addition and sardinella fish oil were increase egg cholesterol (P<0.05) and not significantly (P>0.05) on length storage time of egg and production of quail.